INFORMATION SYSTEM FOR MONITORING POSYANDU ACTIVITIES TO IMPROVE COMMUNITY HEALTH - Marini Umi Atmaja, Dewi; Rahman Hakim, Arif; Basri, Amat; Rimbawan Oprasto, Raditya; Yakub; Gunawan, Jonathan (PPM Telkom University, 2025)
Posyandu (Integrated Service Post) plays a vital role in improving community health by providing essential health services and recording health data. However, observations have shown that the process of recording and processing health data is still done manually, leading to delays in decision-making and inefficiencies in time management. This study aims to develop a web-based information system to monitor Posyandu activities, streamlining the processes of data recording, processing, and reporting, which are essential for health-related decision-making. The research employs the Prototype method and PIECES analysis framework to design and develop the system. The system is built using the PHP programming language and MySQL database. The implementation is carried out on a local network, with functional testing performed using Blackbox testing and software quality assessed using User Acceptance Testing (UAT) through a questionnaire method. The results show that the proposed system improves data processing efficiency, enhances the accuracy of health reports, and supports Posyandu cadres in delivering information quickly and making timely decisions. The system reduces dependency on manual data management, improving overall service delivery. The findings suggest that further research is needed in related areas to enhance system performance and service quality. Additionally, the system should be developed further with the latest technology to ensure effective and efficient health services.